Compara????o dos efeitos do m??todo Pilates realizado em solo e aparelho sobre a aptid??o f??sica relacionada ?? sa??de e fatores psicol??gicos em mulheres sedent??rias - Freitas, Maria Ludmila Menezes de (2015)
The purpose of this study was to determine and compare the influence of Pilates Method (mat Pilates and apparatus Pilates) on the health-related physical fitness and psychological factors of sedentary women. 39 sedentary women (46, 07??4, 82) participated of this study and were randomized and divided into 3 groups: MAT - floor exercises, AP - exercises on apparatus and CO - control. The two experimental groups met 50min / day three times / week for 5 weeks tradicional mat and apparatus pilates programe.Components of health-related fitness was assessed through tests of 1 mile, sit and reach, lumbar flexion, hand grip strength, abdominal in 1 minute and 4 skin folds. For the psychological factors was used EADS- 21 scale. The statistical analyses ANOVA - Split-plot, Kruskal Wallis test and the paired t test showed after 5-week intervention significant differences (p??? 0,05) as improvement in cardiorespiratory fitness (p=0,0001), muscular endurance (p=0,0001), flexibility (p=0,0001), body fat percentage (p??? 0,05), the hand grip strength of the right hand (p??? 0,05), anxiety, depression and stress(p??? 0,05). The results suggest that Pilates Method mat Pilates and apparatus Pilates has a positive effect on the health - related physical fitness and psychological factors of sedentary women.